Estimation of genetic divergence within androgenic regenerants of Capsicum annuum L. ATZ1 × C. frutescens L. F 1 plants using random amplified polymorphic DNA markers - Dorota Olszewska; Aleksandra Niklas-Nowak; Lubosława Nowaczyk (BioTechnologia, 2018)
To prove the androgenic origin of the regenerants obtained from the anther cultures of interspecific F 1 C. annuum L. ATZ1 × C. frutescens L.) hybrid, Random Amplified Polymorphic DNA (RAPD) method was applied. Thirty decamer primers were used in the experiment. The size of the amplified products ranged from 138 to 2369 bp, and their number from 3 to 25 per primer. About 274 loci, 47 of which were polymorphic, were analyzed. The results proved the hybrid status of anther donor plants detected by 20 of the applied primers. Of the 25 analyzed androgenic regenerants, 18 were diploids. The RAPD reactions confirmed their polymorphism in comparison with that of the F 1 hybrid generation, which excluded their origin from somatic cells of the anthers. Moreover, the results demonstrated the existence of a genetic variation among the obtained haploids, which illustrated genetic diversity of the microspores developing in hybrid anther cultures. The results of the experiments proved the utility of the RAPD method in detecting polymorphisms between closely related pepper plants, proving at the same time the effectiveness of androgenesis, regeneration of haploid plants, and spontaneously doubled haploids (DH lines).